Cover Feature: Efficient Blue Phosphorescence in Gold(I)‐Acetylide Functionalized Coinage Metal Bis(amidinate) Complexes (Chem. Eur. J. 70/2020). Issue 70 (16th October 2020) - Feuerstein, Thomas J.; Seifert, Tim P.; Jung, André P.; Müller, Rouven; Lebedkin, Sergei; Kappes, Manfred M.; Roesky, Peter W.
Abstract : The synthesis of linear symmetric ethynyl‐ and acetylide‐ amidinates of the coinage metals is presented. Their photophysical properties were thoroughly investigated over a temperature range of 20—295 K. All compounds show azure, bright blue, or blue‐green microsecond‐long phosphorescence in the solid state. Short lifetimes and quantum yields of up to 41 % were determined. Furthermore, the complexes show pronounced PL in thf solution as well. The KIT logo on the cover represents photography of some of the substances under irradiation with UV‐light. More information can be found in the Full Paper by P. W. Roesky et al. on page 16676 .